Productivity of Three Dwarf Kopyor Coconut Varieties from Pati, Central Java, Indonesia - Ismail Maskromo; Novarianto, Hengky; Sukendah; Sukma, Dewi; Sudarsono, S. (International Coconut Community Journal, 2013)
Pati Dwarf Kopyor coconut originated from Pati, Central Java is one of the Kopyor coconut populations from Indonesia. Three varieties of Pati Dwarf Kopyor coconut, namely: Kopyor Green Dwarf, Kopyor Brown Dwarf and Kopyor Yellow Dwarf out of six potential varieties have been officially released as local superior varieties by the Minister of Agriculture, Republic of Indonesia at the end of 2010. The objectives of this research were to evaluate the stability of Kopyor fruit production among provenances of Pati Dwarf Kopyor coconuts. Evaluations were conducted especially for the three recently released varieties of Kopyor coconuts. Observations were carried out in 2011 and the collected data were then compared with Kopyor fruit production data collected in 2009 -2010. In three different locations, representatives of 10 Kopyor coconut provenances for each Kopyor variety were observed; therefore, a total of 90 trees were evaluated in this experiment. Observations were conducted for number of total bunches per palm, number of total fruits/per bunch, and the number of harvested Kopyor coconut fruits/per bunch. Three bunches were selected for each of the evaluated provenance. Results of the observation indicated that the observed yield and yield parameters of three Pati Dwarf Kopyor coconut varieties fluctuated by the year of observations. However, in general the observed yield and yield parameters among three varieties were similar. The average number of total bunches observed among three varieties evaluated ranged from 9.6-12.1 bunches per palm; the average number of fruits/per bunch ranged from 5.3-12.4; and the average number of harvested Kopyor fruits/per bunch ranged from 2.0-3.8. The estimated number of total fruits/palm/year among the three varieties ranged from 53.8-128.1 and the percentage of Kopyor fruit production observed among the three varieties evaluated ranged from 24.8-38.9 %. The estimated number of total harvested Kopyor fruits/palm/year ranged from 20.5-39.2, respectively. Rainfall pattern might affect directly or indirectly toward yield and yield components of three Pati Dwarf Kopyor coconut varieties.